The sound of silence in association football: Home advantage and referee bias decrease in matches played without spectators - Sors, F.; Grassi, M.; Agostini, T.; Murgia, M. (European Journal of Sport Science, 2020)
Home advantage and referee bias are two well-documented phenomena in professional sports, especially in association football. Among the various factors determining them, the crowd noise is considered as one of the most relevant; yet, the majority of previous studies could not isolate its contribution. The possibility to study the effects of crowd noise - or, better, of its absence - in an ecological context was given by the matches played behind closed doors due to the COVID-19 pandemic. The aim of the present study was to investigate whether home advantage and referee bias still occur (and to what extent) during matches played in absence of spectators. In particular, the focus was on the first and second divisions of the top four countries in the UEFA ranking, for a total of 841 matches behind closed doors. The hypothesis was that, if these phenomena are largely due to the effect of crowd noise, the absence of spectators should reduce their occurrence. Various parameters for each of the two phenomena were considered, and the analyses revealed a reduction of home advantage and the absence of referee bias. The results bring further support to the claim that, among all the factors contributing to home advantage and referee bias, crowd noise has a relevant role. Thus, spectators can significantly contribute to determine the dynamics and the outcomes of professional football matches.